The Impact of Digital Innovation in School Admission on The High School Participation of Students From Poor Families: Case Study of Online PPDB - Fachrizal, Fachrizal; Jasmina, Thia (National Research and Innovation Agency, Indonesia, 2024)
Digital innovation holds a crucial position in enhancing the quality of the education ecosystem in Indonesia. This study assesses the impact of a specific digital innovation in education—the online school admission process (PPDB)—on the participation of students from poor families at the high school level in the Provinces of DKI Jakarta and West Java between 2015 and 2019. Using the Difference-in-Difference method, the research compares regencies/cities that adopt online PPDB with the control variables of the regencies/cities that do not adopt. The findings reveal that the implementation of online PPDB at the high school level led to a 3.28% increase in the school participation of poor students compared to regencies/citiesthat do not implement the online PPDB. Given the significant role of digital innovation in elevating Indonesia's education ecosystem, digital innovation is expected to increase, particularly those facilitating accessible education for the less privileged. However, there are several obstacles still experienced by parents or students regarding the implementation of online PPDB for high school admissions. Future research is encouraged to broaden the sample size, encompassing more provinces, to yield more comprehensive and robust results.